1998
DOI: 10.1074/jbc.273.11.6503
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Ran GTPase-activating Protein by the Small Ubiquitin-related Modifier SUMO-1 Requires Ubc9, an E2-type Ubiquitin-conjugating Enzyme Homologue

Abstract: Covalent modification of the Ran GTPase-activating protein RanGAP1 with the ubiquitin-related protein SUMO-1 promotes its association with Nup358, a component of the cytoplasmic fibrils emanating from the nuclear pore complex (1, 2). In Xenopus egg extracts, Nup358 can be found in a complex with Ubc9 (3), a structural homologue of the E2-type ubiquitin-conjugating enzymes (UBCs). Here we show that a subset of the human homologue of Ubc9 (HsUbc9) colocalizes with Ran-GAP1 at the nuclear envelope. HsUbc9 forms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 27 publications
7
102
0
1
Order By: Relevance
“…Indeed, the known SUMO ligase, PIAS (9-11) had no effect on H4 sumoylation in vivo or in vitro. These data are consistent with previous reports showing that, unlike ubiquitination, an E3 for sumoylation is not absolutely required, and some sumoylation substrates directly bind to E2 (UBC9) (32,33). We have also shown that the N-terminal tail of H4 is a target for linkage of multiple SUMO moieties (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the known SUMO ligase, PIAS (9-11) had no effect on H4 sumoylation in vivo or in vitro. These data are consistent with previous reports showing that, unlike ubiquitination, an E3 for sumoylation is not absolutely required, and some sumoylation substrates directly bind to E2 (UBC9) (32,33). We have also shown that the N-terminal tail of H4 is a target for linkage of multiple SUMO moieties (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…UBC9 is a ligase for an ubiquitin like protein, SUMO (Sampson et al, 2001). SUMO modiĀ®cation is thought to be involved in the nuclear transport of the modiĀ®ed proteins (Lee et al, 1998;Melchior, 2000). RanBPM is a newly identiĀ®ed factor that interacts with Ran (Nishitani et al, 2001), a small GTP binding protein involved in nuclear tra c of many proteins (Izaurralde et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ubiquitylation, for which numerous ubiquitin conjugating enzymes (Ubc's) have been described, the SUMO pathway apparently uses only a single E2 enzyme, Ubc9 (Gong et al, 1997;Johnson and Blobel, 1999;Schwarz et al, 1998;Lee et al, 1998;Saitoh et al, 1998). Through a conserved Cys residue (Cys93), Ubc9 forms a thioester linkage with SUMO prior to conjugation with the target protein.…”
Section: E2mentioning
confidence: 99%